1994
DOI: 10.1021/ma00084a042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of composition heterogeneities in a miscible pair by ESR spectroscopy: poly(styrene-co-maleic anhydride)/ poly(methyl vinyl ether) blends and semiinterpenetrating polymer networks

Abstract: The compatibility of the two components in semiinterpenetraing polymer networks (semi-IPNs) and corresponding linear blends was studied using the nitroxide spin-label and spin-probe methods. The semi-IPNs and blends were composed of poly(styrene-co-maleic anhydride) (P(S-co-MA)) and poly (methyl vinyl ether) (PVME). Stable nitroxide radicals as reporters were covalently attached to P(S-co-MA) via the maleic anhydride groups ("spin labels") or dispersed in the system ("spin probes"). Electron spin resonance (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…15 However, the spin label technique is more sensitive than DSC and it allows a close look at structural heterogeneities in multicomponent polymer systems, on a length scale of <50Å. 12 Our ESR results are in agreement with the high-resolution solid-state 13 C NMR experiments, 1 showing motional heterogeneity.…”
Section: 13supporting
confidence: 74%
See 1 more Smart Citation
“…15 However, the spin label technique is more sensitive than DSC and it allows a close look at structural heterogeneities in multicomponent polymer systems, on a length scale of <50Å. 12 Our ESR results are in agreement with the high-resolution solid-state 13 C NMR experiments, 1 showing motional heterogeneity.…”
Section: 13supporting
confidence: 74%
“…The observation of two co-existing spectral components in the PAA-PEO complex indicated that the SLPEO existed in dynamically different molecular environments owing to local heterogeneity. 12 The fast and slow motion were attributed to the SLPEO located in the PEO-rich, more flexible microphase, and PAA-rich, more rigid microphase, respectively. Although the relative fast-or slow-motion component intensity is not an absolute measure of the number of immobilized or freely rotating spin probes located in the more rigid micro domain or the more flexible micro domain, owing to the simplicity of quantitative analysis, the fast-motion component denoted by F% can be estimated from the ratio of the intensity of the fast motion in the composite spectrum to that of the fast motion in the single spectrum.…”
Section: Resultsmentioning
confidence: 98%
“…This was not the case for purified, polymerised glutenin subunits extracted from gluten. Urea created similar modifications on gluten as heat.Key words: Prolamin; Gluten; ESR; ST-ESR; Temperature; Urea segmental mobility in the proteins in D20 was high (~65%) and increased with temperature.Electron spin resonance (ESR) spectroscopy can yield information about polymer networks by the use of a stable paramagnetic compound [9]. Spin probing informs about the solvent environment, whilst covalent spin labelling reflects the segmental mobility of labelled molecules.…”
mentioning
confidence: 99%
“…Electron spin resonance (ESR) spectroscopy can yield information about polymer networks by the use of a stable paramagnetic compound [9]. Spin probing informs about the solvent environment, whilst covalent spin labelling reflects the segmental mobility of labelled molecules.…”
mentioning
confidence: 99%
“…13,14 The ESR spectra of spin probe molecules, which are dispersed in the polymer matrix, are sensitive to the motional freedom of the probe molecules with rotational correlation times in the range 10 7 -10 11 s. The motional freedom in turn depends on the environment of the host polymer such as temperature and local composition of the polymer matrix. Therefore, the resulting ESR spectra can reveal information on the segmental motion and microstructure of polymer systems.…”
Section: Introductionmentioning
confidence: 99%